2007
DOI: 10.1080/10410230701454015
|View full text |Cite
|
Sign up to set email alerts
|

Human Affection Exchange: XIII. Affectionate Communication Accelerates Neuroendocrine Stress Recovery

Abstract: Contemporary theory in interpersonal communication and health psychology supports the prediction that engaging in affectionate behavior within established relationships has a direct effect on the alleviation of stress symptoms following exposure to an acute stressor. Participants in this study were exposed to a series of standard laboratory stressors and were subsequently assigned either to an experimental group or to 1 of 2 control groups. Those in the experimental group were instructed to write a letter to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 29 publications
5
44
0
Order By: Relevance
“…In a later experiment, Floyd, Mikkelson, Tafoya, et al (2007) found that during episodes of acute stress (in which cortisol levels are typically elevated), expressing affection in writing to a loved one accelerates the return of cortisol to normal levels. Grewen et al (2005) similarly found that nonverbal affectionate interaction reduced cortisol levels for both men and women, and also elevated levels of the neurohypophyseal hormone oxytocin in women (see also Turner, Altemus, Enos, Cooper, & McGuinness, 1999), whereas Floyd, Hesse, and Haynes (2007) found a strong inverse relationship (b ¼ À .85) between expressed affection and glycohemoglobin (an index of average blood glucose level, which is elevated by stress), after controlling for the effects of received affection.…”
Section: Kissing As a Stress-alleviating Behaviormentioning
confidence: 95%
“…In a later experiment, Floyd, Mikkelson, Tafoya, et al (2007) found that during episodes of acute stress (in which cortisol levels are typically elevated), expressing affection in writing to a loved one accelerates the return of cortisol to normal levels. Grewen et al (2005) similarly found that nonverbal affectionate interaction reduced cortisol levels for both men and women, and also elevated levels of the neurohypophyseal hormone oxytocin in women (see also Turner, Altemus, Enos, Cooper, & McGuinness, 1999), whereas Floyd, Hesse, and Haynes (2007) found a strong inverse relationship (b ¼ À .85) between expressed affection and glycohemoglobin (an index of average blood glucose level, which is elevated by stress), after controlling for the effects of received affection.…”
Section: Kissing As a Stress-alleviating Behaviormentioning
confidence: 95%
“…The classic research program led by Pennebaker has convincingly demonstrated that selfdisclosure, particularly those concerning negative experiences, would improve one's mental and physical well-being (e.g., Pennebaker, Barger, & Tiebout, 1989;Spera, Buhrfeind, & Pennebaker, 1994). Recently, using a hormone-based bio-physiological methodology, Floyd and his associates found that expressing feelings in verbal forms not only reduced stress but also enhanced one's recovery from the distressed state of mind (Floyd, Mikkelson, Hesse, & Pauley, 2007;Floyd, Mikkelson, Tafoya, et al, 2007).…”
Section: Underlying Mechanisms Of Disclosure's Positive Effectsmentioning
confidence: 99%
“…Helping or supporting others predicts reduced associations between stress and mortality (Krause, 2006;Okun et al, 2010;Poulin et al, in press) as well as depression (Brown et al, 2008). Laboratory research indicates that people respond to acute stress by increasing their prosocial behavior (von Dawans et al, in press), and that helping behavior reduces physiological response to stress (e.g., Floyd et al, 2007), raising the possibility that prosociality may serve as a coping strategy.…”
Section: Introductionmentioning
confidence: 99%